PELUANG DAN TANTANGAN E-COMMERCE DALAM DUNIA PERBANKAN DAN OTONOMI DAERAH - Darnilawati Darnilawati (Marwah: Jurnal Perempuan, Agama dan Jender, 2010)
The development of E-commerce as a medium of trade is supported by many of today's world economy demands that emphasizes on the aspects of globalization, liberalization, and development of technology and telecommunications to fulfill the needs of trade and consumers. E-commerce changes the operating of trade, especially in the banking institutions. As its implication, “the gates of traditional banks” forced to change to a new paradigm that emphasizes on the relationship between the banks and their customers, as well as between one company and another company and how the benefits of e-commerce in regional autonomy.